Robotic vs Open Surgery for Endometrial Cancer in Elderly Patients: Surgical Outcome, Survival, and Cost Analysis. Issue 4 (1st May 2018) - Lindfors, Anna; Åkesson, Åsa; Staf, Christian; Sjöli, Per; Sundfeldt, Karin; Dahm-Kähler, Pernilla
Abstract : Objective: This study aimed to compare robotic and open surgery in elderly women diagnosed as having endometrial cancer, in terms of costs, survival, surgical outcome, and operating time. Methods: Women 70 years or older undergoing open and robotic surgery for endometrial cancers were included consecutively before and after the introduction of robotic surgery at a tertiary center. Costs were calculated using the case-costing system, cost per patient, including the first 30 postoperative days. Relative and overall survival outcomes were obtained from the Swedish National Cancer Registry and analyzed using the Kaplan-Meier method. Surgical outcomes including operating and anesthesia times, estimated blood loss, hospital stay, and intraoperative and postoperative complications were reviewed. Results: In all, 137 and 141 women 70 years or older were identified to have undergone open and robotic surgery, respectively. The groups showed similar body mass index, comorbidities, and tumor characteristics. No statistically significant differences were seen in costs (robotic €11, 874 vs open €11, 521, P = 0.463) or 5-year survival outcomes (robotic 94% [95% confidence interval CI, 84–105] vs open 87% [95% CI, 78–98], P = 0.529). Robotic surgery was associated with significantly lower estimated blood loss ( P < 0.001) and shorter hospital stay ( P < 0.001) but longer anesthesia time (186 vs 174 minutes; P < 0.05) and operating theater time (205 vs 190 minutes; P < 0.05). There were no significant differences in intraoperative complications, but robotic surgery resulted in fewer postoperative Clavien-Dindo grade II complications. Conclusions: Elderly women can safely undergo robotic surgery for endometrial cancer and could be offered this technique to the same extent as younger patients. They may benefit from shorter hospital stay, decreased blood loss, and postoperative complications, without resulting in higher costs to the health care system or jeopardizing their survival.